2019
DOI: 10.1038/s41598-019-49854-y
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and organic soil management as divergent drivers of resident and active fractions of major soil food web constituents

Abstract: Conventional agricultural production systems, typified by large inputs of mineral fertilizers and pesticides, reduce soil biodiversity and may negatively affect ecosystem services such as carbon fixation, nutrient cycling and disease suppressiveness. Organic soil management is thought to contribute to a more diverse and stable soil food web, but data detailing this effect are sparse and fragmented. We set out to map both the resident (rDNA) and the active (rRNA) fractions of bacterial, fungal, protozoan and me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 92 publications
5
61
0
1
Order By: Relevance
“…Both DNA and RNA were simultaneously extracted from soil samples (2 g each), using a lab-made protocol based on phenolchloroform-isoamylalcohol extraction (Harkes et al, 2019). Quality and quantity of the obtained RNA and DNA was measured with a Nanodrop and Qubit.…”
Section: Dna/rna Extraction and Cdna Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Both DNA and RNA were simultaneously extracted from soil samples (2 g each), using a lab-made protocol based on phenolchloroform-isoamylalcohol extraction (Harkes et al, 2019). Quality and quantity of the obtained RNA and DNA was measured with a Nanodrop and Qubit.…”
Section: Dna/rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…The variable V4 region of bacterial 16S rRNA gene was utilized as target for the analyses of Illumina 16S rDNA sequencing and the V9, V7-V8, V5-V7 regions were utilized as targets for protozoa, fungi, and metazoan 18S rDNA sequencing, respectively. To prepare the samples for sequencing, a two-step PCR procedure was followed as described in (Harkes et al, 2019). In short, locus-specific primer combinations extended with an Illumina read area and the appropriate adapter were used to produce primary amplicons.…”
Section: Pcr Amplification and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of soil type is corroborated by significant effects of soil physico-chemical parameters (soil pH, clay content, soil organic matter content) on the regional scale (Table S5 & Figure S5). Soil types, with their specific physical and chemical properties, are considered to be strong environmental filters for the assembly of microbial communities, sometimes more influential than plant species (Garbeva et al, 2004;Harkes et al, 2019). Importantly, soil types may contribute to explain regional differences in microbial community composition.…”
Section: Soil Type and C/n Ratio As Major Structuring Forces Of Protimentioning
confidence: 99%
“…A study under controlled greenhouse conditions showed a reduction of the relative abundance of plant pathogenic protists was reduced by organic fertilizer amendments, while bacterivores and omnivores increased (Xiong et al, 2018). However, in a field study, plant parasites were favoured by organic fertilization (Harkes et al, 2019). Thus, currently a global and coherent picture of the responses of protistan plant pathogens to fertilization and other anthropogenic changes cannot be inferred.…”
Section: Introductionmentioning
confidence: 98%